Examining Inclusiveness of a Women’s Empowerment Program - Ningrum, Amalia Tri Widya (Departemen Sosiologi Universitas Gadjah Mada, 2024)
This study examines the inclusiveness of a program called Desa PRIMA (Perempuan Indonesia Maju Mandiri) or Women's Village Empowerment Program for Advanced Indonesian Women, which was developed by the Yogyakarta Special Region Government to alleviate poverty and promote gender equality. Specifically, it examines the extent to which the program effectively reaches vulnerable groups of women, including widows, individuals with disabilities, survivors of violence, and other marginalized communities. Employing a qualitative case study approach, this research explores the program’s implementation at Desa PRIMA’s Productive Economic Group (Kelompok Ekonomi Produktif – KEP), Amarta Sejahtera, located in Pandowoharjo Village, Sleman Regency, Yogyakarta. Data were collected through observations, in-depth interviews, and document analysis. Thematic analysis was employed to identify patterns in the program’s inclusiveness. The findings indicate that while the program has a positive impact on women’s collective enterprises by enhancing their confidence, facilitating knowledge-sharing, and providing social support. However, it still faces challenges in effectively reaching vulnerable women. Political interests emerge as a key barrier to the program’s effectiveness, increasing the risk of exclusion and restricting access to essential resources. The study concludes that women’s empowerment programs need to be redesigned to promote greater inclusivity and better align with the needs of their intended target groups. Such efforts are crucial in promoting equitable access to opportunities and resources, particularly for women in vulnerable groups.